Key Influences on Oral Feeding Achievement in Preterm Infants: Insights From a Tertiary Hospital in Indonesia - Putri Maharani Tristanita Marsubrin; Ni Nyoman Berlian Aryadevi; Bernie Endyarni Medise; Yoga Devaera (International Journal of Pediatrics)
Conclusion: This study found significant associations between the time to achieve FOF and factors such as oxygen therapy duration, sepsis episodes, and frequency of blood transfusion. These findings highlight the importance of considering these factors in managing preterm infants. However, a further prospective study is warranted to identify additional factors that influence feeding milestones in preterm infants.